2006
DOI: 10.1159/000090741
|View full text |Cite
|
Sign up to set email alerts
|

Differential Effects of Cooked Beans and Cooked Lentils on Protein Metabolism in Intestine and Muscle in Growing Rats

Abstract: Aims: The effect of diets based on cooked beans or lentils on protein metabolism in intestines and muscles was studied in rats. Method: The cooked seeds were used as the unique protein source in balanced diets (containing 229 and 190 g of crude protein per kg dry matter) fed to young growing rats for 20 days. Their effects were compared with those of the control casein diet in pair-fed rats. Protein synthesis rates in small and large intestines and in gastrocnemius and soleus muscles were determined in vivo, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 52 publications
2
15
0
Order By: Relevance
“…In our earlier studies with legumes added in the diet, protein metabolism in gastrocnemius muscle was decreased, if there was an effect on body-weight gain (31) and was almost unchanged if there was no difference in the body-weight gain (32,33) , which is in accordance with results of the present study. Gastrocnemius muscle is sensitive to the nature of the nutrients derived from the diet (34) and, as a fast-twitch oxidative glycolytic muscle, is a good indicator of the average response of whole skeletal muscle (35) .…”
Section: Discussionsupporting
confidence: 93%
“…In our earlier studies with legumes added in the diet, protein metabolism in gastrocnemius muscle was decreased, if there was an effect on body-weight gain (31) and was almost unchanged if there was no difference in the body-weight gain (32,33) , which is in accordance with results of the present study. Gastrocnemius muscle is sensitive to the nature of the nutrients derived from the diet (34) and, as a fast-twitch oxidative glycolytic muscle, is a good indicator of the average response of whole skeletal muscle (35) .…”
Section: Discussionsupporting
confidence: 93%
“…Several studies have evaluated the effect of plant-based protein sources, i.e., raw faba beans [ 18 , 19 , 20 , 21 ], raw peas, cooked lentils or cooked beans [ 22 , 23 , 24 , 25 , 26 ], soy proteins [ 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 ], faba bean proteins [ 36 ], and wheat proteins [ 33 ] when compared with animal-based protein sources on body protein retention and metabolism in young or old rats, pigs, or humans. All have reported a positive effect of animal proteins on protein metabolism in young animals or humans as compared to plant-based protein sources, regardless of their form, e.g., raw or cooked, protein isolate, or protein hydrolysate.…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, it has been reported that a diet rich in vegetable protein results in a weaker inhibition of postprandial protein degradation in humans, when compared to a diet rich in animal proteins [26]. A specific enhancing effect of lentils or beans protein on small and large intestine masses, protein content and fed state protein synthesis rates has been reported in the literature [27,28]. In humans, a reduction in albumin synthesis and plasma albumin levels occurs when vegetable protein consumption increases [29].…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a reduction in albumin synthesis and plasma albumin levels occurs when vegetable protein consumption increases [29]. Lower muscle mass and protein synthesis rates have also been demonstrated with legume-based diets (lentils, beans or peas) versus casein in animals [28,30-32]. The reasons for these tissue effects are mostly unclear, in particular because the effect of dietary plant protein may be confounded in part by the potential digestive or metabolic effects of a series of associated factors (e.g.…”
Section: Discussionmentioning
confidence: 99%